Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper aims to contribute to the discussion by sketching ways in which the taxation equity-efficiency frontier could be shifted outward in the Netherlands. In a nutshell, we argue that significant efficiency gains could be achieved by shifting the tax burden away from labor, and toward consumption and capital-especially housing. The detrimental impact of the tax-benefit system on labor supply-in particular by mothers-and the insufficient and distortionary use of the value-added tax (VAT) as a revenue-collection mechanism is also highlighted in the paper. This paper also reviews the main features of the Dutch tax system and sketches the contours of a hypothetical tax reform.